AÇÃO DE EDUCAÇÃO EM SAÚDE: BARRACA DA SAÚDE - Silva, Liliane Santos Da; Silva, Tiago Emanuel Vieira Da; Pereira, MicnéiasRóberth; Ribeiro, Isnnara Barbosa Cavalcante; Clemente, Ana Paula Grotti (Gep News, 2018)
Coletânea alusiva aos 40 anos da Faculdade de Nutrição da Universidade Federal de Alagoas (FANUT/UFAL).